2015
DOI: 10.17159/2222-3436/2015/v18n3a4
|View full text |Cite
|
Sign up to set email alerts
|

Institutional forces and divestment performance of South African conglomerates: Case study evidence

Abstract: The history of South Africa serves as a natural experiment in how a changing institutional environment impacts corporate structure. Based on institutional theory, we anticipate higher performance through emulating successful strategies or through restructuring consistent with mimetic isomorphism. Conversely, coercive isomorphism results from restructuring driven by regulation, and we anticipate that they are associated with lower performance. To examine these relationships, we consider divestment by South Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…These isomorphic institutions are discussed below in the Ghanaian context. (King et al 2015;McGaughey et al 2016;Smith et al 2016). Usually, such conformity means acquiring legitimacy for their operation and outreach services (King et al,2015;Trapczynski and Banalieva, 2016).…”
Section: Institutional Theory and The Operation Of Fngos In Ghanamentioning
confidence: 99%
See 3 more Smart Citations
“…These isomorphic institutions are discussed below in the Ghanaian context. (King et al 2015;McGaughey et al 2016;Smith et al 2016). Usually, such conformity means acquiring legitimacy for their operation and outreach services (King et al,2015;Trapczynski and Banalieva, 2016).…”
Section: Institutional Theory and The Operation Of Fngos In Ghanamentioning
confidence: 99%
“…DiMaggio and Powell (1983) indicated that FNGOs are likely to mimic or imitate other organisations which they come into contact with. Thus, FNGOs in their attempt to provide financial services to MSEs are likely to be influenced by their peers or competitors (King et al ,2015). According to Meyer and Rowan (1977), mimetic changes occur when organisations import rules and practices which may not couple properly with internal structures and may cause a wide internal variation in organisational behaviour.…”
Section: Mimetic Isomorphic Institutionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Diversification by South Africa's core mining firms through their acquisition of non-core businesses eventually led to the emergence of six giant conglomerates that dominated the Johannesburg Stock Exchange (JSE), which together represented 80% of market capitalization by 1992. 24 As a result of this development, by the late 1980s South Africa's economy was effectively controlled by six wealthy families. 25 The post-1948 period was thus marked by a coalitional class alliance consisting of white organized labour and conglomerate groupings with investments in mining, finance, and industry, operating in the context of state protection and racialized capitalism.…”
Section: The Shifting Political Economy Of Segregation Autarky and Liberalizationmentioning
confidence: 99%